LOCAL SCOUR AROUND THE SIDE -WEIR ON COHESIVE BED MATERIAL - Saracoglu, Fevziye Ayca; Agaccioglu, Hayrullah (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2022)
The scour process and dimensionless equilibrium scour depths around the rectangular side weir have been studied for the non -cohesive bed material, extensively. In this experimental study, scour of cohesive materials in the vicinity of a rectangular side weir is studied for the first time, 38 runs including different combinations of upstream Froude Number, the length of side -weir, the side weir crest height, water content, clay content and bed shear strength has been conducted for this purpose. Experimental parameters are determined based on a dimensional analysis. Only subcritical flow conditions in a rectangular channel have been considered in this study. The bottom shear strength of cohesive sediment increases with the consolidation time hence the scour depths decrease with consolidation time. The scour depth increased rapidly with time and then asymptotically approached constant values with similar behavior to non -cohesive bed material. For all side weir dimensions, dimensionless scour depths increase with increasing the upstream Froude number and decrease with increasing the side -weir crest height where non -cohesive bed material act similarly. The scour depths has been found to be much smaller for the cohesive bed material when compared to non cohesive material for even stronger stream conditions. A regression equation is proposed for dimensionless equilibrium scour depths depending on dimensionless parameters for cohesive bed,
Keywords: Cohesive sediments; Flow-side weir interactions; Scour; Scour process; Side Weir; SRICOS; FLOW; Environmental Sciences & Ecology